2015
DOI: 10.1007/s10555-015-9595-8
|View full text |Cite
|
Sign up to set email alerts
|

EPLIN: a fundamental actin regulator in cancer metastasis?

Abstract: Treatment of malignant disease is of paramount importance in modern medicine. In 2012, it was estimated that 162,000 people died from cancer in the UK which illustrates a fundamental problem. Traditional treatments for cancer have various drawbacks, and this creates a considerable need for specific, molecular targets to overcome cancer spread. Epithelial protein lost in neoplasm (EPLIN) is an actin-associated molecule which has been implicated in the development and progression of various cancers including bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 45 publications
2
54
0
Order By: Relevance
“…Previous studies evaluating EPLIN in cancer progression have identified loss of EPLIN in aggressive cancer and suggest a regulatory role for EPLIN as a tumor suppressor . Additionally, several mechanisms have been reported for the regulation of EPLIN expression, including ERK, EGF, DNp73 and p53, and provide important insight into how EPLIN may be regulated at a functional or expressional level.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous studies evaluating EPLIN in cancer progression have identified loss of EPLIN in aggressive cancer and suggest a regulatory role for EPLIN as a tumor suppressor . Additionally, several mechanisms have been reported for the regulation of EPLIN expression, including ERK, EGF, DNp73 and p53, and provide important insight into how EPLIN may be regulated at a functional or expressional level.…”
Section: Discussionmentioning
confidence: 93%
“…Prostate cancer is the second most common cancer in the UK and accounts for >11,000 cancer‐related deaths . Epithelial protein lost in neoplasm (EPLIN) is a molecule that is frequently lost in cancer and has been implicated in the initiation of epithelial–mesenchymal transition, in addition to having tumor suppressive roles in cancer progression and development …”
Section: Introductionmentioning
confidence: 99%
“…Importantly, a reduction of hCDC14A and eplin levels is frequently observed in colorectal carcinoma and is associated with poor prognosis in cancer patients (Fig. 5 I and J) (20,34,35). Collectively, we propose that the balance of eplin phosphorylation that is maintained by the antagonistic activities of ERK and hCDC14A toward conserved phosphorylation sites on eplin plays a key role in regulating actin dynamics to modulate cell migration and adhesion of both normal and transformed cells (Fig.…”
Section: Discussionmentioning
confidence: 69%
“…Downregulation of eplin frequently occurs in cancer tissues and contributes to the epithelia-to-mesenchymal transition (EMT) that enhances cancer cell metastasis and chemo-resistance of tumors (23,(33)(34)(35)(36)(37).…”
Section: Phosphomentioning
confidence: 99%
“…quite recently showed that doliculide treatment of p53 wild‐type cancer cells alters up to 13% of senescence‐related genes at nontoxic concentrations. Like tubulin, actin is also implicated in the metastatic process …”
Section: Mollusk‐derived Anticancer Agentsmentioning
confidence: 99%